Structural and electrochemical performance studies for nanocomposites of carbon with Fe3C or Mn-Substituted (Fe3C/Fe3O4) as anodes for Li-batteries - Gangwar A.; Sharma A.; Shaw S.K.; Singh Meena S.; Prasad N.K. (My University, 2025)
The nanocomposites of Fe3O4 or Fe3C or Fe3O4/Fe3C with carbon are exploited as anode materials for Li-ion batteries due to their higher theoretical capacities. The present work depicts the charging capacity of nanocomposites (~5–25 nm) of carbon with Fe3C or MnrFe3-rC/MnsFe3-sO4 (where 0.2 ≤ r + s ≥ 0.7). These composites are synthesized using an inexpensive urea assisted sol–gel route which are then heat treated at 700 °C in an inert atmosphere. The x-ray and electron diffractions validate the presence of Fe3C, Fe3O4, and carbon phases in the samples. The X-ray photoelectron spectroscopy depicts the oxidation states for the elements of nanocomposite M7FOC. Mössbauer spectroscopy further supports the findings of earlier studies. The electrode kinetics and the electrochemical performance for the materials are assessed by Voltammograms and Galvanostatic lithiation/delithiation plots. The specific charge capacities and Coulombic efficiencies with respect to cycle numbers at room temperature are also evaluated. The optimum specific capacity of ~1261 mAh g−1 is observed for M7FOC sample whereas its reversible specific lithiation capacity is found to be around 841 mAh g−1 after the initial cycle at the rate of C/20. © 2020 Elsevier B.V.